KEPEMIMPINAN TRANSFORMASIONAL DALAM PENINGKATAN KEPUASAN KERJA KARYAWAN - Mutmainatul Mardiyah (JABE (Journal of Applied Business and Economic), 2016)
The purpose of this study is to describe how transformational  leadership increases employees’s  job satisfaction.  The  research was conducted at Islamic Elementary School of An-Nizomiyah, located at Jalan Masjid Al Fajri, Pejaten, South Jakarta.It showed that Transformational Leadership and Employees’ job satisfaction at this school are generally good.  The achievement oftransformational leadership indicators reaches at 82.77%, and the achievement of employees’ job satisfaction indicators reaches at 81,66%.  It can be said that transformational leadership has been successfully implemented to increase employees’s  job satisfaction at this school. Based on the research result, the employees’ job satisfaction could be enhanced by increasing the indicators of transformational leadership through idealized influence, individualized consideration, intellectual stimulation, and inspirational motivation.  It proves that transformational leadership can increase employee’s job satisfaction.